Stereotactic Pelvic Reirradiation for Locoregional Cancer Relapse. Issue 1 (January 2021) - Kinj, R.; Doyen, J.; Hannoun-Lévi, J.M.; Naghavi, A.O.; Chand, M.E.; Baudin, G.; Ferrero, J.M.; François, E.; Evesque, L.; Borchiellini, D.; Benezery, K.; Bondiau, P.Y.
Abstract: Aims: Up to 40% of patients who have received radiation for a pelvic malignancy will develop locoregional recurrence in the previously irradiated volume. Stereotactic body radiotherapy (SBRT) has been used in the oligometastatic setting, and provides an ablative approach ideal for reirradiation. The purpose of this study was to evaluate the outcomes after SBRT reirradiation of extraosseous recurrences in the pelvis. Materials and methods: This single institution retrospective study evaluated patients treated with SBRT reirradiation in the pelvis from January 2011 to February 2018. Patients with more than five oligometastatic lesions, >7 cm in size, and recurrence within the prostate were excluded. Results: In total, 30 patients were treated with SBRT with a median follow-up of 29.4 months. The primary tumour sites were most commonly rectum (30.8%) and prostate (30.8%). The median time interval between irradiation for the primary and SBRT reirradiation was 48 months (3–245). The typical reirradiation treatment was 35 Gy in five fractions, the median gross tumour volume size was 10.2 (0.3–110.5) ml and the most common target was the iliac nodes (40%). There were three (10%) acute grade 3 toxicities and no late grade 3 or more toxicities. At 12/24 months, local relapse-free survival, metastasis-free survival, progression-free survival and overall survival were 67.7%/50.7%, 67%/41.7%, 34.8%/14.9% and 83.2%/62.5%, respectively. On univariate analysis, improved local control was associated with low gross tumour volume (<10 ml) ( P  = 0.003) and prostate primary ( P  = 0.02), but was no longer significant on multivariate analysis. The proximity of organ at risk to the target did not significantly correlate with worse toxicity ( P  = 0.14) or tumour coverage (gross tumour volume: P  = 0.8, planning target volume: P  = 0.4). Conclusion: SBRT pelvic reirradiation in oligometastatic patients is a safe and effective treatment modality. Careful consideration should be taken with larger tumour size, as it may be associated with worse oncological and toxicity outcome. Highlights: 35 Gy in five fractions was a safe and effective regimen for stereotactic pelvic reirradiation. Reirradiation permitted a local control of 68% at 12 months and 42% at 24 months. Acute and late grade 3 toxicity rates were low: 10% and 0%, respectively.